ISLAMIC PERSPECTIVE ON BIRTH CONTROL: ISSUES AND PROSPECTUS - Bilal Ahmad Wani; Dr. Rafiq Anjum (Fakultas Agama Islam Universitas Wiralodra, 2019)
Birth control, also known as contraception and fertility control are the methods or devices used to prevent pregnancy. Planning, provision and use of birth control is called family planning. The History of birth control is as old as Islam itself. The Arabs used to practice it during the days of Jahaliyah. After the advent of Islam, the muslims continued the process and is said to have got permission with moderation from the prophet SAW. The moderation he did was to approve the practice of Azl as a measure to birth control. Birth control or family planning is not a new issue rather it has remained a burning issue from the advent of Islam as it is today. It is a concept for all people and all nations of the world irrespective of people’s religious alienations.